PCSK9 in Haemostasis and Thrombosis: Possible Pleiotropic Effects of PCSK9 Inhibitors in Cardiovascular Prevention - Paciullo, Francesco; Momi, Stefania; Gresele, Paolo (Thrombosis and Haemostasis, 2019)
Since increased cholesterol levels are crucial in determining the development of atheroma, their reduction represents a mainstay in primary and secondary cardiovascular prevention. The most recent spectacular advancement in cholesterol-lowering therapy is represented by proprotein convertase subtilisin/kexin type-9 (PCSK9) inhibitors. Although their benefit over currently available treatments has been ascribed primarily to their strong low-density lipoprotein (LDL)-cholesterol reducing action, several clues suggest that PCSK9 inhibitors may also influence platelet function and blood coagulation. PCSK9 knockout mice develop less venous and arterial thrombosis and show reduced in vivo platelet activation upon arterial injury. In patients with acute coronary syndromes (ACSs) treated with P2Y12 inhibitors, a direct association between PCSK9 serum levels and residual platelet reactivity was found. A direct correlation between urinary excretion of 11-dehydro-thromboxane-B2, a marker of in vivo platelet activation, and circulating PCSK9 levels was reported in patients with atrial fibrillation. Moreover, recombinant human PCSK9 added in vitro to human platelets potentiated activation induced by weak agonists. Finally, blood clotting factor VIII (FVIII), which is associated with stroke and ACS risk, is cleared from the circulation by members of the LDL receptor (LDLR) family. Given that PCSK9 degrades LDLR, it is conceivable that PCSK9 inhibitors by enhancing the expression of LDLR may slightly decrease circulating FVIII, in this way contributing to the prevention of cardiovascular events. This review aims to discuss the possible and hypothetical interactions between PCSK9 and the haemostatic system and to examine the possible pleiotropic effects of PCSK9 inhibitors in cardiovascular prevention.
Keywords: atherothrombosis; CD36; dyslipidaemia; FVIII; LOX-1